Interjurisdictional Company Taxation in Europe, the German Reform and the New EU Suggested Direction - Marcel Gérard (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper proposes an analysis of two major tax events which occurred in the European Union in 2001, the move of Germany from imputation to exemption and the objective announced by the EU Commission to provide EU businesses with a consolidated corporate tax base for their EU-wide activities. In particular we examine as to whether those tax systems are able to become perfectly integrated tax systems by which we mean neutral tax systems with respect to financial, organisational and locational decisions of a multijurisdictional firm.
Keywords: 330; corporate taxation; tax competition; European Union.